Types and meaning of food in the Inaguration Penghulu ceremony in Nagari Kambang Timur - Maisa, Dela Sukma; Elida, Elida (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
traditional leaders or customary density (KAN), bundo kanduang, the community. Data collection techniques through observation, interviews and documentation. Data analysis used is data reduction, data presentation and conclusions. The results of this study indicate that the types of food at the batagak penghulu ceremony in Nagari Kambang Timur are cakes that must be served onde-onde, banana chips, kue kembang goyang, lapek bugih, nasi lamak jo sagun. The food that must be served is rice, meat curry, badulang rice. Additional food: cubadak curry, raburan curry, chicken curry, fried fish, kalio jariang. The tools used for processing include cauldrons (pans), mandai (basins), steamers (steamers), rocking flower molds, grated banana chips, strainers, grated coconut, wood stoves, large cooking pots, banana leaves, wooden spoons, knives, lado stones (pout). Utensils for serving such as trays, piriang samba, dumplings of rice, small plates. Tools for carrying food such as trays, serving covers, wraps, scarves, throws with lids, piriang samba. The traditional food made for the penghulu batag ceremony has a meaning that contains useful messages for all people.